Solving the Clinker Dilemma with Hybrid Output-based Allocation - Frédéric Branger; Misato Sato (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper proposes an innovative solution to distribute free allowances to the cement sector under emissions trading systems, called hybrid output-based allocation (OBA). We demonstrate that unlike many of the allocation methods currently being used, our design provides incentives which are aligned with the mitigation options available to this sector in the short to medium term. Specifically, it increases the incentive to improve the carbon intensity of clinker production; reduces the incentive to import clinker to avoid carbon costs; increases the incentive to use more low-carbon clinker alternatives to produce cement; and finally it reduces excess allocation and reduces incentives to inflate production volumes to obtain more free allowances. The hybrid OBA does not, however, provide incentives to reduce the consumption of cement or to bring about break-through technologies, hence should be considered as a mid-term solution to aid the decarbonization of the cement sector in conjunction with other support mechanisms.
Keywords: Q50; Q54; H23; 330; Emissions Trading; Output-based Allocation; Climate Policy; Cement sector; Clinker Dilemma